The Impact of Educational Facilities and Infrastructure Management on Student Learning Outcomes and Process: A Case Study at SMA Al-Yasini Kraton Pasuruan - Arika Ilmi Hulailah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
This study was motivated by the importance of educational facilities and infrastructure management as a collaborative process to utilize school assets effectively and efficiently in order to support the quality of the learning process. The purpose of this study was to determine the effect of facilities and infrastructure management on the learning process. This study uses a quantitative method with a descriptive and associative approach. The research population consists of 50 teachers, with a Proportional Random Sampling technique that produced 30 respondents. Data collection was conducted through questionnaires, interviews, and documentation. Data analysis included validity testing (Product Moment Correlation) and reliability testing (Cronbach's Alpha), as well as simple linear regression analysis, T-test, and coefficient of determination using SPSS. The results showed that the management of facilities and infrastructure at Al-Yasini Kraton Pasuruan High School was in the acceptable category. Furthermore, a coefficient of determination ($R^2$) of 0.32 was obtained, indicating that the variable of facilities and infrastructure management (X) had a 32% influence on the variable of the learning process (Y). It can be concluded that facilities and infrastructure management has a significant influence and is in the good category for improving the learning process. Effective and efficient management of facilities and infrastructure is essential to support the success of teaching and learning activities at school.